CUSTOMER LOYALTY OF KANGGO RIKO COFFEE SHOP SIDOARJO - Noerchoidah; Christina Menuk Handayani; Wahyu Priyanto (Universitas Dinamika, 2021)
This study examines the effect of price, product diversity, facilities, and location on customer loyalty at Kedai Kopi Kanggo Riko Sidoarjo. A total of 120 customers were used as samples in this study with incidental sampling technique. Data were analyzed using SPSS software. The results of the study describe a significant influence between price and customer loyalty, product diversity affects loyalty, facilities affect customer loyalty, location affects customer loyalty. Simultaneously price, product diversity, facilities, and location affect customer loyalty. These results provide evidence that Kedai Kopi Kanggo Riko Sidoarjo can increase customer loyalty by emphasizing price factors, product diversity, facilities, and location.